The Effect of Cooperative Type Number Heads Together and Concept Mapping Learning Models on Student's Learning Activity and Student Learning Outcomes in Class V Science Study of SD Negeri 11 Rantau Selatan - Lehawati, Lehawati; Sutopo, Adi; Sekarwinahyu, Mestika (BIRCU, 2020)
One of the lessons that make students more active is cooperative learning. Cooperative learning is a way of learning in which students of all abilities work together in small groups to achieve goals. This model prioritizes student-centred learning and students can interact with their friends in solving problems. The cooperative model has several types, including the cooperative model, Number Head Together. Concept Mapping was first developed by Tony Buzan, a mathematician, psychologist and researcher. Concept Mapping helps students to improve learning outcomes. Sampling using purposive sampling technique. while the sample in the study consisted of 2 classes, namely class 5 a as the experimental class 1 for Testing the Effect of the Cooperative Learning Model type Number Head Together and Concept Mapping on Student Learning Activities and Outcomes, and Class V b as the experimental class 2. The Cooperative Learning Model Type Number Head Together and the Concept Mapping Learning Model have a significant effect on Learning Activeness and Student Learning Outcomes in Class V Science Subjects at SD Negeri 11 Rantau Selatan. However, when analysed on the aspect of a stronger influence on Activities and Learning Outcomes, based on the results of the above calculations, it is obtained data that the Concept Mapping Learning Model has a stronger effect on student learning activeness compared to learning outcomes in science subjects. The Number Head Together Learning Model has a stronger influence on the results than the student learning activity in science learning materials.